2023
DOI: 10.1007/s00455-023-10584-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Prevalence and Characteristics of Oro-bulbar Involvement in Children and Adults with SMA Type 2 and 3 Using a Multimodal Approach

Federica Trucco,
Francesca Salmin,
Andrea Lizio
et al.

Abstract: Bulbar and jaw muscles are impaired in patients with Spinal Muscular Atrophy (SMA) but the assessment of their severity and progression are limited by the lack of age-appropriate and disease-specific measures. We investigated mastication and swallowing in children and adults with SMA, sitters and walkers. In a 2-year multicentre cross-sectional prospective study, lip and tongue strength (Iowa Oral Performance Instrument), chewing and swallowing (Test of Masticating and Swallowing Solids), active mouth opening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…The max pressure index thus likely reflects the known severity in the different SMA subgroups. It is also in line with Trucco et al (2023)'s recent publication indicating that tongue strength was below normative data in 47% of patients in a children cohort of SMA type 2-3 patients [16].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The max pressure index thus likely reflects the known severity in the different SMA subgroups. It is also in line with Trucco et al (2023)'s recent publication indicating that tongue strength was below normative data in 47% of patients in a children cohort of SMA type 2-3 patients [16].…”
Section: Discussionsupporting
confidence: 91%
“…These two questions would be best described by the intensity rather than by the frequency of these complaints. Other studies on swallowing in SMA patients used objective mouth opening measure and did not focus on frequency [16]. Thus, we should consider removing these two questions from the SFAQ in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further data on bulbar function in adult patients with SMA under gene-based therapies are scarce. Data available for nusinersen also support an overall positive effect on bulbar symptoms in adult patients with SMA, yet not as clearly and robustly [ 29 – 32 ]. A direct comparison of both therapies is challenging due to the significant differences in the clinical features of the two patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…Both measuring tools are patient-reported outcome measures and are thus limited in their objectivity and could be biased by patients' expectations of a new therapy. Furthermore, a recent study assessing oro-bulbar involvement in adults and children with SMA using objective measures such as lip and tongue strength and mouth opening revealed that patients´ perception of bulbar function often differs from objectifiable deficits, some of which are not subjectively perceived by patients [ 32 ]. This limits the interpretability of patient-reported outcome measures in this field.…”
Section: Discussionmentioning
confidence: 99%